Coupling of electromagnetic waves into wires: experiments and simulations - Duffy, Alistair Paul (1993)
Electromagnetic Compatibility (EMC) problems may occur in many environments. This Thesis considers a particular sub-set of coupling within shielded enclosures. The actual systems studied are the coupling between a dipole and either one or two rods in a screened room and the effect of a cavity and apertures on a signal travelling along a wire.